Evaluating the implementation and impact of a literature circle among 8th grade students of Unidad Educativa BilingüeTorremar. - Tapia Álvarez, César Vicente (2018)
The issue detected at Unidad Educativa Bilingüe Torremar was analyzed through action research. The first part of the project covered two surveys for students in order to analyze their current reading habits and the attitudes towards them. An interview was also applied to two teachers which explained the importance and advantages of the implementation of the presented project. The literature review projects information about reading habits, reading attitudes and how they can be improved in order to affect positively students’ critical thinking and their EFL skills. It was detected that students’ reading skills needed to be improved and strengthened. Therefore, a proposal was design to fulfil that aim. The proposal consisted in the implementation of literature circles during English classes with 8th grade students of Unidad Educativa Bilingüe Torremar. Class observations were also applied in order to d iagnose and analyze how literature circles affect students’ reading skills and their performance evolution along the sessions.